Risk Assessment of Type 2 Diabetes Mellitus Depending on The Degree of Activity of Rheumatoid Arthrits - Sultаnova M. X.; Sherbekova D. U.; Mirkhamidov M.V (Scholars Digest Publishing, 2023)
Objective: to assess the risk of developing type 2 diabetes mellitus using the FINDRISC questionnaire in individuals with rheumatoid arthritis, depending on the degree of disease activity. Materials and Methods: The study included 75 people: 55 (73.3%) women and 20 (26,6%) men aged 18 to 60 years with rheumatoid arthritis. The ten-year risk of developing diabetes was assessed using the FINDRISK scale (Finnish Type 2 Diabetes Risk Assessment Form). All respondents were divided into three groups depending on the level of rheumatoid arthritis activity according to the Desease activity index 28-ESR scale (DAS28-ESR). Statistical processing of the material was carried out using the IBM using the Kruskal-Wallace, Mann-Whitney, and Spearman coefficients. Results and Discussion: in the frequency structure of risk factors for the development of type 2 diabetes, abdominal obesity (73.5%) and overweight (62%) prevailed. Important differences between the comparison groups were found according of eating vegetables .A direct correlation was found between the degree of activity of rheumatoid arthritis and the risk of developing diabetes mellitus according to the FINDRISC scale Conclusion: a high degree of activity of rheumatoid arthritis increases the risk of developing type 2 diabetes in the next decade of life. The use of the FINDRISK questionnaire can serve as an effective tool for assessing the risk of type 2 diabetes in individuals with rheumatoid arthritis.
Keywords: rheumatoid arthritis, FINDRISK, type 2 diabetes mellitus.